2012
DOI: 10.3109/10428194.2012.734613
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate and nitrite intake and risk of non-Hodgkin lymphoma

Abstract: Although established risk factors such as immunodeficiency and viral infections may be responsible for a portion of non-Hodgkin lymphoma (NHL) cases, the vast majority of NHL cases remain unexplained. The role of dietary nitrate and nitrite in NHL risk is of interest since they are precursors of N-nitroso compounds and nitrosoureas have been shown to induce B and T-cell lymphomas in animal studies. However, few studies have evaluated the potential association between consumption of nitrate and nitrite intake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Limited number of studies available precluded any meaningful subgroup analyses for linear dose-response meta-analyses. Eighteen [ 6 , 9 , 15 , 22 , 23 , 34 , 35 , 42 , 43 , 45 , 46 , 48 , 50 , 52 54 , 61 , 62 ] and twelve [ 5 , 6 , 9 , 34 , 42 , 43 , 45 , 46 , 48 , 50 , 52 , 53 ] studies were included in the dose-response analysis for dietary nitrate and nitrite respectively. The summary RR for each increase by 10mg/day for dietary nitrate intake was 0.99 (95%CI = 0.98-1.00) with moderate to high heterogeneity (I2 = 63.4%).…”
Section: Resultsmentioning
confidence: 99%
“…Limited number of studies available precluded any meaningful subgroup analyses for linear dose-response meta-analyses. Eighteen [ 6 , 9 , 15 , 22 , 23 , 34 , 35 , 42 , 43 , 45 , 46 , 48 , 50 , 52 54 , 61 , 62 ] and twelve [ 5 , 6 , 9 , 34 , 42 , 43 , 45 , 46 , 48 , 50 , 52 , 53 ] studies were included in the dose-response analysis for dietary nitrate and nitrite respectively. The summary RR for each increase by 10mg/day for dietary nitrate intake was 0.99 (95%CI = 0.98-1.00) with moderate to high heterogeneity (I2 = 63.4%).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, two studies were identified from the reference lists of the retrieved and review articles. After reading the full texts, 8 case-control and 4 follow-up studies that reported the correlation between nitrate or nitrite consumption and risk of NHL published between 1996 and 2013 were selected [14][15][16][17][18][19][20][21][22][23][24][25] . Table 1 displays the fundamental characteristics of the articles included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…During the past decades, the relationship between risk of NHL and nitrate or nitrite consumption have been investigated in several epidemiological publications, yet the results are contradictory. Some surveys failed to show positive or negative associations [14][15][16][17][18][19][20][21] , while others have revealed significant correlations [22][23][24][25] . When no specific trend can be ascertained from any individual investigation, combining a number of independent studies can reveal hidden associations through meta-analysis.…”
mentioning
confidence: 99%
“… 13 , 16 Other potential mechanisms which might underlie an increased risk of NHL risk with red and processed meat consumption, involve NOCs, which have been linked to the risk of lymphoma in humans. 44 , 45 …”
Section: Discussionmentioning
confidence: 99%